Response to “The Feasibility and Acceptability of a Mobile Application for Oral Health Education Among Adults in Rwanda” [Letter] - Wijaya A; Prabowo RY; Jayadi L (Clinical, Cosmetic and Investigational Dentistry)
Avid Wijaya,1 Rahmadyo Yudhi Prabowo,1 Lukky Jayadi2 1Medical Record and Health Information Department, Poltekkes Kemenkes Malang, Kota Malang, Jawa Timur, Indonesia; 2Department of Pharmacy, Poltekkes Kemenkes Jakarta 2, Kota Jakarta Selatan, DKI Jakarta, IndonesiaCorrespondence: Avid Wijaya, Poltekkes Kemenkes Malang, Jl. Besar Ijen 77C, Malang, Indonesia, Email avidwijaya@poltekkes-malang.ac.id